The Pleasure of His Company Antoinette Sibley and Anthony Dowell interviewed - Craine, Debra (Dance Books Ltd., Alton,Hampshire (UK), 2004)
Antoinette Sibley and Anthony Dowell talk about Ashton. PALABRAS CLAVE: Frederick Ashton, Anthony Dowell, Antoinette Sibley, Royal ballet.
Dentro del apartado "Celebrating Frederick Ashton. 17 September 1904 - 19 August 1988".